Penerapan Metode Combined Compromise Solution (CoCoSo) dalam Pemilihan Franchise Minuman - Marito, Julita; Nainggolan, Wahyuni Betris; Mahendra, Gede Surya (LPPM STT Terpadu Nurul Fikri, 2024)
The research in this journal is motivated by the beverage franchise industry, which has become one of the most dynamic global business sectors. This article examines applying the Combined Compromise Solution (CoCoSo) method to the decision-making system (SPK) in selecting beverage franchises. The beverage franchise data that we use consists of 9 brands that are pretty famous among the public, such as Kopi Kenangan, Es Teh Indonesia, Teh Poci, Calais Tea, Puyo Puyo, Gulu Gulu, Kopi Kulo, Xi boba, Kopi Yor. In the process of data collection, we use observation and research. The data analysis process is carried out using the combined compromise solution method, one of the multi-criteria decision-making (MCDM) methods that can be used to select alternatives based on the calculation of criteria weights. This method can facilitate the determination of beverage franchises because it is more effective and efficient in calculating and ranking. Through the decision-making system that has been developed, the value of the beverage franchise can be generated based on predetermined criteria. Calculation of beverage franchises using CoCoSo shows the results of the calculation of the highest preference value obtained by the Puyo Puyo beverage franchise with a final value of 2.3436 and the lowest preference value obtained by the Kopi Kenangan beverage franchise with a final value of 1.3385.